Students’ Ability in Writing Paragraphs Using Structure of The Paragraph in Argumentative Essay By The Sixth Semester of English Study Program of Muhammadiyah University of Bengkulu - Yudi Agus Prananda (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2016)
This research is aimed to know “How is Students’ Ability in Writing Paragraph Using Structure of The Paragraph in Argumentative Essay by The Sixth Semester of English Study Program of UMB. The objective of this research was to identify and describe the students’ ability in writing paragraph using structure of the paragraph in argumentative essay by the sixth semester of English Study Program of UMB. This research used descriptive method. The population of this research was 164 students from all of classes at the sixth semester of English Study Program of UMB. This research used random sampling. The samples were taken from 50% of the total number of population, where the samples were 84 students. The instrument of this research used writing test. The result of this study, the paragraph in argumentative essay was 54.58. From the data were 2 students had very good score, 18 students were good, 16 students were poor, and 48 students were very poor. And the students’ mean score of each aspect in writing are: in introduction was 6.47, in body was 8.13, in conclusion was 5.75, in topic sentences was 8.71, in supporting sentences was 7.96, in concluding sentences was 7.95, in sentences structure was 4.99, and in grammar and mechanics was 4.15.The result of analysis showed that the average of the students’ ability in writing paragraph using structure of the paragraph in argumentative essay was qualified “very poor”. Based on the result above, the researcher suggest that the lecturer; It is suggested for the lectures to analyzed the students’ difficulties in composing essay itself and find out the solving problem in order to make the students more comprehend about compose the essay. The students need practice to write a good paragraph by using essay organization, paragraph organization, sentences structure, grammar and mechanics correctly